Drivers of Green Innovations: The Impact of Export Intensity, Women Leaders, and Absorptive Capacity - Galbreath, Jeremy (Springer Netherlands, 2017)
© 2017 Springer Science+Business Media B.V. Little research has considered the potential influence of distant, external pressures on the implementation of firms’ ‘green’ innovations, nor how internal firm resources might moderate this relationship. By combining institutional and resource-based theories and examining 649 firms in Australia, I find that export intensity is positively associated with green innovations. Further, as women in leadership roles increase in firms, the relationship strengthens between export intensity and green innovations. The results also suggest that greater levels of absorptive capacity among firms strengthen the relationship between export intensity and green innovations. Contributions of the findings are discussed along with limitations and future research opportunities.